Renewal of pastoral-religiosus in the diocese of Włocławekin the light of resolutions Synods Bishop Maciej Łubieński (1631-1641) - GRĘŹLIKOWSKI, KS. JANUSZ (Prawo Kanoniczne, 2018)
Dar reform and renewal of pastoral offered to the Church the mid-sixteenth century in the resolutions of the Council of Trent, implemented and put into practice the particular Churches by successive centuries been zealously and fruitfully undertaken by Bishop Matthias Łubieński and with great gusto on three synods, two diocesan in 1634 and 1641 r. and at the Synod for archdeaconry of Pomerania in 1640. Their resolutions have become not only an opportunity to carry out pastoral renewal of the Church of Wloclawek, but also helped to deepen knowledge of and respect for the law and become an effective instrument to preserve the unity and discipline of the Church in the diocese, as well as the introduction of the Tridentine reform. Placed firmly in the conciliar decrees and resolutions of provincial synods statutes governed the many sectors of pastoral life of the diocese then Kuyavian-Pomeranian activating pastors, and engaging religiously and morally lay faithful. This outstanding legislator, reformer and supporter of the renewal of the Tridentine Church and its pastoral structures, he realized that the renewal of pastoral care and repair of life of religious and moral needs to find its origin in the reform of the clergy, maintaining discipline and discipline of the Church and in the life and behavior of the clergy in line with the spirit the priestly vocation. Resolutions of the Synod of Bishop Łubieński were a manifestation of his zeal legislative, - a reformist. Strongly urged by the harmonization of laws relating to the sacramental life, the discipline of the clergy and the development of religious life, while the development of pastoral care. His legislative activity, legal and pastoral was as structured, broad and comprehensive. She referred first to the fact purely legislative activity, and also had a practical nature, as refer to and serve the renewal of pastoral care and religious life of the faithful. Pastoral renewal efforts also served to reinforce the organization deaneries and the revival of activity deans, among others, in the control of pastoral remind parish priests of their duties in the field of studying parishioners, care for the sick and the poor, regulations relating to the defense of the Catholic faith threatened the Reformation, the regulations relating to teach the truths of the faith, teaching catechetical exercise and the sacraments, worship of God, and affairs liturgical celebrations. It all had to serve the post-conciliar renewal of pastoral ministry in the Church Wloclawek.